Phylotyping and ColV plasmid-associated virulence genotyping of E. coli isolated from broiler chickens with colibacillosis in Iran. (September 2016) - Mohsenifard, Elham; Asasi, Keramat; Sharifiyazdi, Hassan; Basaki, Mehdi
Abstract Avian pathogenicEscherichia coli (APEC) strains are responsible for significant losses to the poultry industry in many parts of the world. Although, many serotypes ofE. coli are non pathogen, a relatively few number of serotypes carry virulence genes which make them damaging for chicken and other poultry. Previously, high prevalence of virulence genes carried on plasmid and/or chromosomal DNA has demonstrated in APECs obtained from different countries. The aim of the present study is characterization ofE. coli isolated from broiler chickens with pericarditis and femoral head necrosis (FHN) associated with colibacillosis based on the phylogenetic typing and ColV plasmid-carried virulence genotyping. In present study, 290E. coli isolates from pericardial sac (n  = 120) and lesions of femur (n  = 100) of chickens exhibiting clinical and necropsy findings of colibacillosis from poultry farms in Fars province, Iran, besides 70 isolates from the intestinal content of apparently healthy birds were phylotyped and examined for the presence of seven virulence genes (ompT, hly, iss, iutA, iron, tsh, andcvaC ) carried on ColV plasmid by multiplex PCR. Phylotyping analysis showed that the most of the APEC isolates fell into the phylogenetic group A and subgroup A1 . Also, virulence genotyping indicated that ColV plasmid-carried virulence genes were significantly higher in APEC compared to avian fecalE. coli (AFEC). Based on the results of this study, having several virulence genes of ColV plasmid and belonging to the phylogenetic group A might provide useful characteristics for the better identifying Iranian APECs. However, the link between avianE. coli pathogenicity and different phylotypes and genotypes needs more future works involving a larger number of samples to be confirmed.